INVESTIGATION OF “GREEN” APPROACH TRAJECTORY FOR FULL EXPLOIT OF THE BENEFITS OF SINGLE EUROPEAN SKY - Bogunenko, Nikolay; Khomenok, Anastasia (Proceedings of National Aviation University (archive), 2012)
The article deals with main directions of European Clean Sky concept, investigation of the influence of changing of glide slope angle on the engine operation mode during approach phase, analysis of advantages and disadvantages of changing of glide slope angle.